Overcharge‐Induced Phase Heterogeneity and Resultant Twin‐Like Layer Deformation in Lithium Cobalt Oxide Cathode for Lithium‐Ion Batteries. Issue 32 (11th September 2022) - Oh, Juhyun; Lee, Seung‐Yong; Kim, Hwangsun; Ryu, Jinseok; Gil, Byeongjun; Lee, Jongki; Kim, Miyoung
Abstract: Overcharging is expected to be one of the solutions to overcome the current energy density limitation of lithium‐ion battery cathodes, which will support the rapid growth of the battery market. However, high‐voltage charging often poses a major safety threat including fatal incendiary incidents, limiting further application. Numerous researches are dedicated to the disadvantages of the overcharging process; nonetheless, the urgent demand for addressing failure mechanisms is still unfulfilled. Herein, it is revealed that overcharging induces phase heterogeneity into layered and cobalt oxide phases, and consequent "twin‐like deformation" in lithium cobalt oxide. The interplay between the uncommon cobalt(III) oxide and the deformation is investigated by revealing the atomistic formation mechanism. Most importantly, abnormal cracking is discovered in the vicinity of the cobalt oxide where structural instability induces substantial contraction. In addition, surface degradation is widely observed in the crack boundary inside the particle. As unintentional overcharging can occur due to local imbalance in state‐of‐charge in severe operating conditions such as fast charging, the issues on overcharging should be emphasized to large extent and this study provides fundamental knowledge of overcharge by elucidating the crack development mechanism of layered cathodes, which is expected to broaden the horizon into high voltage operation. Abstract : Overcharged lithium cobalt oxide is investigated in depth to understand the microstructural interplay between the phase heterogeneity and the crack formation during overcharging. Direct observation of the cobalt oxide phases nearby the abnormal crack provides the cracking mechanism of twin‐like deformation. Moreover, the degradation occurring at the crack boundary emphasizes the negative impact of overcharging in relation to physical damages.